The collocation approach to Moho estimate - Riccardo Barzaghi; Ludovico Biagi (Annals of Geophysics, 2014)
In this paper, the collocation approach to Moho estimate is presented. This method is applied to the inversion of gravity data that can be complemented by Moho depth information coming from e.g. seismic information. In this context, a two layers model is considered and discussed in order to give a general theoretical framework for the inversion method. A body with two inner constant density layers and an inner separation surface between is considered and a uniqueness theorem is proved for the estimability of the separation surface given the gravity outside the body itself. Based on this result, a discussion is given on the estimation of the Moho depths based on terrestrial gravity observations. The observation equation is presented and its local planar approximation is derived. The application of the collocation method to the estimate of Moho depths is then studied and discussed in relationship to the planar observation equation. Also, numerical tests are presented. To this aim, the collocation inversion algorithm is implemented and tested on simulated data to prove its effectiveness. The results show that the proposed method is reliable provided that proper data reductions for model discrepancies are taken into account.